Regulating the building of contracts in the Islamic economy - Fayze Elharche, Ahmed (Finance and Business Economies Review, 2020)
Contracting is considered one of the foundations of the economic construction of trade exchanges in countries, and since its construction on solid foundations is a cause for economic and social advancement, Islamic legislation has been keen on the proper construction of the contract. The study sought to clarify the wisdom of restricting some contracts in economic activity. The study concluded that the construction of contracts in the Islamic economy has laid the foundations of justice and charity between the two parties to the contract, and that legislation excluded types of contracts due to their negative role in economic activity, and the study showed the wisdom of preventing some contracts and other legislation because of the achievement of the interests of the contractors and an affirmation of the purposes of the Sharia.